The expression and significance of NF-ÎºB, MMP1, and MMP2 in rats with abdominal aortic aneurysm - Xie, Zhilei; Fang, Tao (Cellular and Molecular Biology, 2020)
This study aimed to investigate the expression and significance of NF-ÎºB, matrix metal protein1 (MMP1), and matrix metal protein2 (MMP2) in rats with abdominal aortic aneurysm (AAA). 48 Wistar rats were collected, then they were divided into an experiment group and a control group (n=24). The rats in the experiment group were used to carry out an abdominal aortic aneurysm modeling, while the rats in the control group were infused with a same dose of saline through catheters. qRT-PCR and ELISA were used to detect the expressions of EGF and VEGF-C in skin tissues and mRNA of NF-ÎºB, MMP1, and MMP2 in their abdominal aorta. A vernier caliper was used to measure the diameter of their abdominal aorta. Western blot was used to detect the expressions of NF-ÎºB, MMP1, and MMP2 in their abdominal aorta. In the experiment group, the abdominal aorta of the rats expanded to some extent after they were infused compared to that before they were infused (P< 0.05), and the abdominal aorta of them was significantly larger than that of the rats in the control group. On the 3rd week after modeling, the abdominal aorta of the rats expanded more obviously compared to that after they were infused for a while in the experiment group, and the expansion rate of the diameter was (57.19 ± 4.67)% (P< 0.05). Protein expression levels of NF-ÎºB, MMP1, and MMP2 in the abdominal aorta of the rats increased significantly in the experiment group compared to those of the rats in the control group (P<0.05). The increase of NF-ÎºB, MMP1, and MMP2 may be related to the pathogenesis of abdominal aortic aneurysm in abdominal aortic aneurysm models of rats.